Cytoplasmic retention and nuclear import of 5S ribosomal RNA containing RNPs. - Rudt, F (1996)
Nuclear export of newly transcribed 5S ribosomal RNA in Xenopus oocytes occurs in the context of either a complex with the ribosomal protein L5 (5S RNP) or with the transcription factor IIIA (7S RNP). Here we examine nuclear import of 5S RNA, L5 and TFIIIA. The 5S RNP shuttles between nucleus and cytoplasm and only 5S RNA variants which can bind to L5 gain access to the nucleus. The 7S RNP is retained in the cytoplasm. Only TFIIIA which is not bound to 5S RNA is imported into the nucleus. As a novel mechanism for cytoplasmic retention, we propose that RNA binding masks a nuclear localization sequence in TFIIIA. In contrast to the nuclear import of L5, import of TFIIIA is sensitive towards the nuclear localization sequence (NLS) competitor p(lys)-BSA, suggesting that these two proteins make use of different import pathways.